The role of environmental taxation and environmental incentives to reduce environmental pollution manifestations in the urban environment - Emad Ghfoory, Ghefar; Khaleefah, Nada; Yousif Hamdan, Maarb (Journal of Planner and Development, 2023)
The aim of studying the role of environmental taxation is to reduce or mitigate the problem of environmental pollution and obtain a clean environment. And the importance of research lies in the fact that environmental taxation is one of the basic tools to achieve environmental balance. As it is considered one of the sustainable economic tools that focuses on the concept of environmental taxes and fees. Therefore, the incentives stimulated institutions to invest in clean energy and use environmentally friendly machines. Through it, the rules of the competition are updated in favor of organizations that respect the environment so that they can obtain a green competitive advantage. And that the main issue in the industries is the result of the technical and technological progress taking place at the present time, which has led to a deterioration in the urban environment and the depletion of its natural resources. In this research, some concepts about the components of the urban environment, environmental pollution, environmental taxes, and taxes were addressed, and the experiences of some countries were presented. The most important findings of the research are that collection and environmental incentives have a major role in reducing pollution.